Hubungan Prenatal Yoga, Nyeri Punggung dan Kualitas Tidur terhadap Kecemasan pada Ibu Hamil Trimester III - Sri Ayu Ningsih; Eka Afrika; Merisa Riski (Universitas Batanghari Jambi, 2022)
Anxiety in pregnancy is an adverse risk factor for both mother and baby. At the Nagaswidak Public Health Center, out of 10 pregnant women, there were 8 third trimester pregnant women who experienced anxiety in facing the labor process. The purpose of this study was to determine the relationship between prenatal yoga, back pain and sleep quality on the anxiety of third trimester pregnant women. The research method used an analytical survey with a cross sectional approach with all third trimester pregnant women in the Nagaswidak Public Health Center area. The sampling technique was carried out by accidental sampling with a total sample of 44 respondents. Data collection using a questionnaire sheet. Data analysis using univariate analysis and bivariate analysis using chi square test. The results showed that there was a relationship between prenatal yoga, back pain and sleep quality with anxiety in third trimester pregnant women in the Nagaswidak Public Health Center working area in 2021. The conclusion is that there is a relationship between prenatal yoga , back pain and sleep quality on the anxiety of third trimester pregnant women at the Nagaswidak Health Center in 2021.